Koeksistensi Antara Tradisionalitas dan Modernitas Perihal Ekonomi dan Budaya di Kota Surakarta - , IQBAL BASYARI, Hasrul hanif, SIP., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traditional institutions in Indonesia never get a clear status in the government. Although previously traditional institutions is an important part in the formation of the Indonesian nation, but many traditional institutions was abandoned nowadays. Indonesia prefers the modern institutions to handle the formal government to execute the government. But in the last decades the traditional institutions began to strengthen. Finally the strengthenin traditional institutions must be joggle with modern institution that holds the formal institution in several regions in Indonesia. The goal of this research to explain the pattern of relations between the traditional institutions with modern institutions in Surakarta in the economic and cultural affairs during the Mayor Joko Widodo. This research uses the concept of a case study with qualitative research. Amid the many studies that discuss the strengthening of traditional institutions, this research into a new outlook in view of the traditional institutions amid the dominance of modern institutions in Indonesia. Surakarta Kingdom and Surakarta government are coexistence. But their relationship is joggle in the economic affair during Mayor Joko Widodo. The relationship in the economic affair is competition, as occurs in the labeling objects of cultural heritage Surakarta Kingdomâs property. The relationship in the cultural affair is competition and complementary. Competition occurs in the struggle for cultural authority, and complementary in terms of culture functions as a tourism asset. connecting these two institutions is important nowadays, because until now the relationship between traditional institutions and modern institutions are still a lot of type of competition. Even if there were patterned complementary relationship, itâs because the modern institutions and traditional institutions still need to increase financial cooperation. If both of these institutions in a unified logic, the synergies between the two institutions are becoming increasingly powerful and traditional institutions get clarity on the status of the modern times.